Proceedings CVPR IEEE Computer Society Conference on Computer Vision and Pattern Recognition 1996
DOI: 10.1109/cvpr.1996.517161
|View full text |Cite
|
Sign up to set email alerts
|

Shadows and shading flow fields

Abstract: Many presume that parsing the shadows out of an image is a high-level task, because of the global nature of the shadow formation process. But shapefrom-shading algorithms are low-level, in the sense that they seek solutions (surface normals or depth values) directly from image intensities. A dilemma arises: since shape-from-shading involves an illumination term, shadows must first be identified. We show that a structure in.termediate between intensitees and surfaces -the shading flow field ~ provides a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Intuitively, this theory makes sense because the relationship between 2D image properties and 3D surface properties is different for different cues. However, we and others have previously suggested that measurements similar to the ones proposed here likely play a role in the estimation of shape from shading and specular (mirror-like) reflections (26)(27)(28)(29). This theory suggests that at least for the early stages of processing, texture, shading, specular reflections, and possibly some other cues could share more in common than previously thought.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Intuitively, this theory makes sense because the relationship between 2D image properties and 3D surface properties is different for different cues. However, we and others have previously suggested that measurements similar to the ones proposed here likely play a role in the estimation of shape from shading and specular (mirror-like) reflections (26)(27)(28)(29). This theory suggests that at least for the early stages of processing, texture, shading, specular reflections, and possibly some other cues could share more in common than previously thought.…”
Section: Discussionmentioning
confidence: 52%
“…Although additional processing would be required to regularize the orientation field and to derive a complete estimate of the 3D shape from these measurements, the correspondence between the outputs of the filters (which measure local 2D image structure) and the true 3D surface orientations is surprisingly good. We, and others, have argued previously that orientation fields could play an important role in the estimation of shape from shading and specular reflections (26)(27)(28)(29). Here, we suggest that similar mechanisms could also play a role in the estimation of shape from texture.…”
mentioning
confidence: 65%
“…Furthermore, orientation is explicit not only in ODTs but also in motion and optical flows, and therefore the theory developed in this article is directly applicable to motion-based segregation. More importantly, orientation is implicit in other visual cues that take part in the segregation process, in particular, shading (23) and color (24). Therefore, the results presented here imply that the role of these other cues in early vision and segregation should be revisited.…”
Section: Discussionmentioning
confidence: 98%
“…The curvature estimator in (17) is the tangential or isophote curvature. The normal (or gradient flow line) curvature [17] can be computed by exchanging the v and w coordinates in (12) and (13).…”
Section: Ymentioning
confidence: 99%
“…For noisy oriented patterns, segmentation fails, making these methods useless. The isophote (tangential) curvature (the second derivative along the isophote divided by the gradient magnitude) and the normal curvature [17] are segmentation-free [7], [8], [17], but also fail on these images. There are three reasons for this [5]: 1) The gradient is zero on ridges and in valleys.…”
Section: Introductionmentioning
confidence: 99%